2009
DOI: 10.2217/pgs.09.142
|View full text |Cite
|
Sign up to set email alerts
|

Nevirapine-Induced Hepatotoxicity and Pharmacogenetics: A Retrospective Study in a Population from Mozambique

Abstract: Our preliminary results confirm the contribution of the ABCB1 c.3435C>T SNP in nevirapine-induced hepatotoxicity risk and, at the same time, suggest the necessity for further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 23 publications
3
40
1
2
Order By: Relevance
“…In another HIV-positive South African population, the allele frequency of the 516G4T SNP was 43%, with 23% being homozygous and 41% heterozygous (Gounden et al, 2010). In a population from Mozambique, the 516G4T SNP was found in 41-49% of individuals, with 17-23% of individuals being homozygous (Ciccacci et al, 2010). The 785A4G SNP was found in 43-45% of these individuals, with 20% having a homozygous genotype.…”
Section: Cyp2b6*6 (516g4t and 785a4g)mentioning
confidence: 91%
See 3 more Smart Citations
“…In another HIV-positive South African population, the allele frequency of the 516G4T SNP was 43%, with 23% being homozygous and 41% heterozygous (Gounden et al, 2010). In a population from Mozambique, the 516G4T SNP was found in 41-49% of individuals, with 17-23% of individuals being homozygous (Ciccacci et al, 2010). The 785A4G SNP was found in 43-45% of these individuals, with 20% having a homozygous genotype.…”
Section: Cyp2b6*6 (516g4t and 785a4g)mentioning
confidence: 91%
“…Brown et al (2012) reported the 516G4T SNP to be significantly correlated with increased nevirapine exposure in a Malawian population. However, no significant association was found between the 516G4T SNP and nevirapine-induced hepatotoxicity in a Mozambiquan population (Ciccacci et al, 2010). More studies involving nevirapine plasma concentrations and CYP2B6 polymorphisms are thus needed to clarify these differences in observations.…”
Section: Cyp2b6*6 (516g4t and 785a4g)mentioning
confidence: 93%
See 2 more Smart Citations
“…The polymorphism ABCB1-3435C>T has been associated with a decreased risk of hepatotoxicty in patients receiving NVP [37][38][39]; nevertheless, this observation is paradoxical since a lower expression of P-gp would lead to a greater accumulation of NVP inside the hepatocytes.…”
Section: Cyp2b6-g516gg (Common Genotype)mentioning
confidence: 99%